Comparing the Levels of Non-citation of Iranian Journals on Health in Persian and English in Scopus Database - Safieh Tahmasebi; Zahra Foroughi; Reza Alizadeh-Navaei (Journal of Mazandaran University of Medical Sciences, 2017)
Background and purpose: Publication of scientific journals in every country is recognized as one of the main ways for publishing and development of science and knowledge. The aim of this research was to compare the differences in non-citations of Iranian journals in Persian and English on health indexed in Scopus during 2011 and 2015.